What patients want to know, and what we actually tell them: The ABIDE project. Issue 1 (16th December 2020) - Fruijtier, Agnetha D.; Visser, Leonie N.C.; Bouwman, Femke H.; Lutz, Rogier; Schoonenboom, Niki; Kalisvaart, Kees; Hempenius, Liesbeth; Roks, Gerwin; Boelaarts, Leo; Claus, Jules J.; Kleijer, Mariska; de Beer, Marlijn; et al.
Abstract: Background: We studied to what degree and at whose initiative 25 informational topics, formerly identified as important, are discussed in diagnostic consultations. Methods: Audio recordings of clinician–patient consultations of 71 patients and 32 clinicians, collected in eight Dutch memory clinics, were independently content‐coded by two coders. The coding scheme encompassed 25 informational topics. Results: Approximately half ( Mdn  = 12) of the 25 topics were discussed per patient during the diagnostic process, with a higher frequency among individuals receiving a dementia diagnosis ( Mdn  = 14) compared to others ( Mdn  = 11). Individual topics ranged from being discussed with 2/71 (3%) to 70/71 (99%) of patients. Patients and/or care partners rarely initiated topic discussion (10%). When they did, they often enquired about one of the least frequently addressed topics. Conclusion: Most patients received information on approximately half of the important informational topics. Providing the topic list to patients and care partners beforehand could allow consultation preparation and stimulate participation.